Porcine Cysticercosis in Southeast Uganda: Seroprevalence in Kamuli and Kaliro Districts - C. Waiswa; E. M. Fèvre; Z. Nsadha; C. S. Sikasunge; A. L. Willingham (Journal of Parasitology Research)
The recent recognition of neurocysticercosis as a major cause of epilepsy in Uganda and changes in pig demography have lead to a need to better understand the basic epidemiology of Taenia solium infections in pigs and humans. Human exposure is a function of the size of the animal reservoir of this zoonosis. This is the first field survey for porcine cysticercosis to investigate the prevalence of antigen-positive pigs across an entire rural district of south-east Uganda. In our field surveys, 8.6% of 480 pigs screened were seropositive for the parasite by B158/B60 Ag-ELISA. In addition, of the 528 homesteads surveyed 138 (26%) did not have pit latrines indicating a high probability of pigs having access to human faeces and thus T. solium eggs. This study thus indicates the need for better data on this neglected zoonotic disease in Uganda, with a particular emphasis on the risk factors for infection in both pigs and humans. In this regard, further surveys of pigs, seroprevalence surveys in humans and an understanding of cysticercosis-related epilepsy are required, together with risk-factor studies for human and porcine infections.